Obtención de extractos etanólicos de hojas de tabaco (Nicotiana Tabacum) para inhibición del hongo Fusarium Oxysporum (2024)
The most widely used fungicides currently contain chemical compounds such as triazoles, strobilurins, benzimidazoles and dicarboximides, designed to inhibit or eliminate fungi according to their mechanisms of action. However, many of these fungicides have negative side effects on soils, such as infertility and contamination of nearby waters, as well as on plants that serve as food for local animals. For this reason, research has been promoted towards the development of fungicides from organic raw material to mitigate these side effects of synthetic products. The current project seeks to evaluate three methods of ethanolic extraction and the capacity of the tobacco leaf to inhibit the fungus Fusarium Oxysporum, using an alkaloid present in the tobacco leaf plant (Nicotine). This alkaloid interferes with the cell membrane of the fungus, inhibits fungal enzymes and stops its growth. The project seeks to identify the most effective extraction method in terms of yield, inhibition capacity, efficiency, economic analysis, minimization of environmental and social risks. With these results, it is planned to conceptualize a pilot plant for the medium-scale production of the organic fungicide. This plan will include the definition of the block diagram, mass balances, equipment costs, compliance with regulations, safety measures and control systems necessary for the operation of the plant. This approach will allow establishing a solid foundation for the scalability of the selected ethanolic extraction and the subsequent implementation of the organic fungicide in the agricultural industry.